2005
DOI: 10.1007/s10545-005-0110-1
|View full text |Cite
|
Sign up to set email alerts
|

State regulation and response inhibition in children with ADHD and children with early‐ and continuously treated phenylketonuria: An event‐related potential comparison

Abstract: Our electrophysiological data support the state regulation hypothesis of ADHD. Only the children with PKU had more problems in inhibiting pre-potent responding than controls, which is in accord with the prefrontal dysfunction hypothesis of PKU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 57 publications
2
24
0
7
Order By: Relevance
“…13,14 Inhibitory control was tested with a slow and fast event rate Go ⁄ No-Go task, which targets both alerting and executive functions supported by frontostriatal and limbic brain areas, and has differentiated ADHD groups from other clinical groups and controls. 15,16 The consistent finding has been that Go ⁄ No-Go performance deteriorates under slow event rate conditions, supporting the view that a deficiency in effort ⁄ activation systems constitutes the key deficit in ADHD. 17 Therefore, the present study sought to examine sustained attention and inhibitory control in children with ADHD or FASD from a differential diagnostic perspective.…”
mentioning
confidence: 65%
“…13,14 Inhibitory control was tested with a slow and fast event rate Go ⁄ No-Go task, which targets both alerting and executive functions supported by frontostriatal and limbic brain areas, and has differentiated ADHD groups from other clinical groups and controls. 15,16 The consistent finding has been that Go ⁄ No-Go performance deteriorates under slow event rate conditions, supporting the view that a deficiency in effort ⁄ activation systems constitutes the key deficit in ADHD. 17 Therefore, the present study sought to examine sustained attention and inhibitory control in children with ADHD or FASD from a differential diagnostic perspective.…”
mentioning
confidence: 65%
“…These studies showed that slow and inaccurate RT performance in the condition with a long ISI was accompanied by reduced parietal P3 amplitude indicating less effort allocation (Wiersema et al, 2005;Wiersema et al, 2006).…”
Section: Psychopharmacologymentioning
confidence: 88%
“…The response inhibition (Barkley, 1997;Quay, 1997) and cognitive energetic models (Sergeant, 2000;Sergeant, 2005) have lent themselves readily to consideration using ERP tasks/methodology. Studies examining the effect of energetic factors on inhibitory processing report at least partial support for the Cognitive Energetic Model (Wiersema et al, 2005b;Wiersema et al, 2006;Benikos and Johnstone, 2009;Johnstone et al, 2010b;Johnstone and Galletta, in press). …”
Section: Discussionmentioning
confidence: 99%
“…-- Table 5 about hereIn a study using a visual Go/Nogo task, children with AD/HDcom showed slow and variable responding and a reduced P3 amplitude in the slow event-rate condition, seen as indicating a lack of adjustment of effort required to meet the task demands (Wiersema et al, 2005b). In a study with fast and slow presentation of a Go/Nogo task, the relationship between P3 amplitude and Go RT indicated poor effort allocation in the slow condition, with a reduced Nogo-N2 in the fast condition for children with co-morbid AD/HD and ODD, but not an AD/HD-alone group (Wiersema et al, 2006).…”
Section: Interaction With Energetic Factorsmentioning
confidence: 99%